2015
DOI: 10.1103/physrevb.92.045415
|View full text |Cite
|
Sign up to set email alerts
|

Growth mechanism of silicene onAg(111)determined by scanning tunneling microscopy measurements andab initiocalculations

Abstract: Scanning tunneling microscopy has been used to real-time study the growth of silicene on Ag(111) in the 200-533-K temperature range. We show that the growth mode depends strongly on the deposition temperature T. At T = 300 K and above, the formation of silicene results from the exchange between surface Ag atoms and Si atoms, which are inserted in the substrate top layer. Density functional theory calculations confirm that Si insertion is thermodynamically favored, and we propose an energetic model for explaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
56
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 49 publications
8
56
0
Order By: Relevance
“…1(c)). The two other structures that also grow at the same time are identified as the (4 × 4) and (√13 × √13 − α) silicene phases in agreement with the structures observed in the temperature range of 230-250°C [5,18,19]. We note that the proportion of the (√13 × √13 − β) phase with respect to the two other phases decreases as the coverage approaches 1 ML.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…1(c)). The two other structures that also grow at the same time are identified as the (4 × 4) and (√13 × √13 − α) silicene phases in agreement with the structures observed in the temperature range of 230-250°C [5,18,19]. We note that the proportion of the (√13 × √13 − β) phase with respect to the two other phases decreases as the coverage approaches 1 ML.…”
Section: Methodssupporting
confidence: 81%
“…1 shows the evolution of the surface as the Si coverage increases. At low coverage, the surface consists of strips that form at step edges, consistent with the literature for similar growth temperatures [18]. The baseline of the strips is lower than the upper silver terrace.…”
Section: Methodssupporting
confidence: 58%
“…Silver appears to be appropri-ate for silicene growth since: (i) the Ag-Si phase diagram shows non-miscibility of the solid phases, (ii) Ag and Si lattice constants are in 3/4 ratio and (iii) their similar electronegativity should result in a small charge transfer between the Si layer and the substrate. However, joint experimental studies and DFT calculations have revealed a non-negligible interaction between Si and Ag [24,[27][28][29][30][31] which results in the loss of the electronic properties predicted for the FSS. Depending on both deposition rate and temperature [15,16,19,27] …”
Section: Introductionmentioning
confidence: 99%
“…A first identification in 2007 of a ‘graphitic silicon layer’ was proposed on Ag(100) , followed by the observation of ordered Si nanoribbons on Ag(110), and from 2010, several structures of Si on Ag(111) were described as silicene layers with different epitaxial orientations on the substrate . However, it has been shown recently that large interaction occurs between the silicene layer and the Ag substrate, whether it is on the (110) or on the (111) surface , leading to an hybridisation of the Ag and of the silicene states .…”
Section: Introductionmentioning
confidence: 99%
“…These findings show that, during deposition, the interaction between Si and Ag substrate is much more important than what was originally thought. This, therefore, questions the actual structure of some of the phases observed during the formation of the Si layer, and for which the formation of a Si–Ag surface alloy during growth is now also considered .…”
Section: Introductionmentioning
confidence: 99%